2010
DOI: 10.1007/s11605-009-1113-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of C-Reactive Protein Levels and Long-Term Survival after Neoadjuvant Therapy and Esophagectomy for Esophageal Cancer

Abstract: Preoperative CRP levels are an independent prognostic marker for survival after neoadjuvant treatment in patients with esophageal cancer and may be of value in the re-staging process after neoadjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
(45 reference statements)
3
38
3
Order By: Relevance
“…For example, C-reactive protein concentration has been reported to predict survival in esophageal cancer patients. 38,[46][47][48] However, C-reactive protein tests are not routinely available in many hospitals. In contrast, NLR and PLR tests are easy to perform, less expensive, and readily available.…”
Section: Discussionmentioning
confidence: 99%
“…For example, C-reactive protein concentration has been reported to predict survival in esophageal cancer patients. 38,[46][47][48] However, C-reactive protein tests are not routinely available in many hospitals. In contrast, NLR and PLR tests are easy to perform, less expensive, and readily available.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein is produced in the liver and its production is regulated by pro-inflammatory cytokines such as interleukin (IL)-6, IL-1 and tumor necrosis factor (TNF)α (26)(27)(28). Several previous studies demonstrated that a pre-operative high C-reactive protein level was inversely correlated with survival of patients with esophageal cancer (15)(16)(17)(18). In these studies, the cutoff value of C-reactive protein ranged from 0.5 to 1.0 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…Low serum albumin concentration, often in combination with elevated C-reactive protein, is reported to be a predictor of poor prognosis in various types of cancers including colorectal cancers (12)(13)(14). In esophageal cancers, previous studies have also shown that serum C-reactive protein as a biomarker of systemic inflammation is useful for predicting the prognosis of patients undergoing esophagectomy (15)(16)(17)(18). However, whether such serum biomarkers correlate with the outcome of pre-operative therapy and survival of patients undergoing multimodal treatment is not clear at present.…”
Section: Introductionmentioning
confidence: 99%
“…In patients that underwent neoadjuvant therapy followed by esophagectomy, patients with normal CRP levels had a significant survival advantage compared to patient with an elevated CRP (median survival 65.4 moths and 5-year survival 52.1% compared to median survival 18.7 months vs 5-year survival 23.3%, p=0.027). (Zingg, Forberger, Rajcic, Langton, & Jamieson 2010) Data for other acute phase proteins in esophageal cancer is limited. An et al showed in a small study that SAA and HAP were elevated in patients with esophageal cancer.…”
Section: Acute Phase Proteins In Cancermentioning
confidence: 99%